Quinoa as source of type 1 ribosome inactivating proteins: A novel knowledge for a revision of its consumption. (16th April 2021) - Landi, Nicola; Ruocco, Maria Rosaria; Ragucci, Sara; Aliotta, Federica; Nasso, Rosarita; Pedone, Paolo V.; Di Maro, Antimo
Graphical abstract: Highlights: Ingestion of quinoa seeds gave intestinal disorders. These disorders were generally attributed to phytochemicals (e.g.: saponins). Actually, Quinoa seeds and sprouts contained also a toxic protein, named quinoin. Quinoin was a type 1 ribosome inactivating protein. Quinoin was cytotoxic against both human fibroblasts and keratinocytes cells. Abstract: This study investigates on the presence of toxic proteins in quinoa seeds. To this aim, a plethora of biochemical approaches were adopted for the purification and characterization of quinoin, a type 1 ribosome-inactivating protein (RIP) contained in quinoa seeds. We determined its melting temperature (68.2 ± 0.6 °C) and thermostability (loss of activity after 10-min incubation at 70 °C). Considering that quinoa seeds are used as a food, we found that quinoin is cytotoxic against BJ-5ta (human fibroblasts) and HaCaT (human keratinocytes) in a dose- and time-dependent manner. Moreover, in an in vitro digestive pepsin-trypsin treatment, 30% of quinoin is resistant to enzymatic cleavage. This toxin was found in seeds (0.23 mg/g of seeds) and in sprouted seeds obtained after 24-h (0.12 mg/g of sprout) and 48-h (0.09 mg/g of sprout). We suggest a thermal treatment of quinoa seeds before consumption in order to inactivate the toxin, particularly in sprouts, generally consumed raw.